(3efThQ GdZjHIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje MOhO bGFe GdOjf Edi Ggd GdQVG hGdJSdje Cgd GdWgGQI aGMaXhG ENhGf GdOjf eYGde GdJhMjO hGdGjeGf s
(3BNQgG (B:s
(3ceG GMQege ef jJbQH Edjg HCHhGH SHHgG CjGSG ef GdXgQ hGdYR hGdfUQ hGdSdGe hGdMeO dehdGfG hMOg hGdTcQ dhdjg YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B29s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis